Career readiness among low-income Muslim students - Choirudin Choirudin; I Nyoman Sudana Degeng; Dedi Kuswandi; Purnomo Purnomo; Aprezo Pardodi Maba (Institute of Advanced Engineering and Science, 2022)
This study investigated the context of career readiness for Muslim students from low-income families and its’ correlation among thinking styles and self-efficacy. There were 302 participants consisted of 85 males (28%) and 217 females (78%) with an average age of 20.03 years. The analysis results showed no significant correlation between students' thinking styles based on age and place of residence. However, the difference in age correlated to students thinking styles. There was also a correlation between gender and age toward students' self-efficacy with social persuasion. The analysis showed a significant positive correlation between career readiness and the legislative, liberal, hierarchical, global, executive, local, anarchic, oligarchic, and internal conservative, oligopoly, and internal. Furthermore, significant positive correlation between self-efficacy and career readiness. The higher the students’ career readiness will be the higher their self-efficacy mastery experience. The findings further confirmed the significance of different thinking styles, self-efficacy, and the context of career readiness for Muslim students from low-income families.